Job satisfaction and job performance of hotels during Covid 19 pandemic: how the role of innovative work behaviour and organizational citizenship behaviour? - Amelda Pramezwary; Juliana Juliana; Ira B Hubner; Vasco Adato H Goeltom; Rudy Pramono Rudy Pramono; Calen Calen; Agus Purwanto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The purpose of this study was to analyze the variable Innovative work behavior (IWB) on performance, Variable Innovative work behavior (IWB) on Job Satisfaction (JS), the variable: Organizational citizenship behavior (OCB) on Job Performance (JP) and the variable Organizational citizenship behavior ( OCB) to Job Satisfaction (JS). This research method includes explanatory quantitative research, The independent variables in this study are OCB and innovation culture which affect the dependent variable performance and job satisfaction. The population in this study are star hotels in Tangerang City, which amount to 66 hotels. This study uses simple random sampling method to determine the sample of respondents. The research instrument used was an online questionnaire via google form. For data analysis use software SmartPLS 3.3.3 . The results of this study are Innovative work behavior (IWB) has a positive and significant effect on work performance (JP), Variable Innovative work behavior (IWB) has a positive and significant effect on Job Satisfaction (JS), Job Satisfaction Variable (JS) has a positive and significant effect on Job Performance (JP), Organizational citizenship behavior (OCB) variable has a positive and significant effect on Job Performance (JP), Organizational citizenship behavior (OCB) variable has a positive and significant effect on Job Satisfaction (JS ), Innovative work behavior (IWB) variable has a positive and significant effect on Job Performance (JP) through Job Satisfaction (JS), Organizational citizenship behavior (OCB) variable has a positive and significant effect on Job Performance (JP) through Job Satisfaction (JS).